Outcomes after Surgery for Malignant Pancreatic Neuroendocrine Tumors - Ghalib Azeez Hawramy, Omar Hama; Seerwan Abdullah, Karzan; M.M. Salih, Barham; Hussein A. Kasnazani, Qalandar; Taib Gharib, Dana; Ahmed Mohammed, Dara (Kurdistan Journal of Applied Research, 2019)
The aim of the study is to declare the role of surgery in potentially curative malignant pancreatic neuroendocrine tumors, in term of prognosis, survival and complications after the surgical procedures. Does the surgery play a significant role in the best patient’s interest even in metastatic pancreatic neuroendocrine tumors? Clinical and pathological factors that changed the outcomes were also analyzed. It is retrospective, case series study. All patients who were undergoing surgery for malignant pancreatic neuroendocrine tumors from 2013 to 2018. Results show that, sixteen patients were recruited with a mean age at diagnosis of 49.31 years, (ranging from 19-80 years). There were 8 male and 8 female patients. Common symptoms were abdominal pain 12 (75%) of them three cases had clinical jaundice 3 (18.8%) and one case had acute pancreatitis and pancreatic necrosis. One (6.3%) patient had functional tumor, and the rest 15 (93.8%) were nonfunctional tumors; all of the patients were sporadic pancreatic neuroendocrine tumors. Overall morbidity was (43.8%) with no perioperative mortality. The median follow-up period was 23 months, ranging from 5-68 months. Recurrence occurred in four cases with a median disease-free interval of 9.5 moths with grade of differentiation (P-value 0.027), lymph node metastases (P-value 0.027) and tumor stage (P-value 0.017) were associated with recurrent disease. The overall 5 year survival was 81.2% and the disease free survival was (75%) at 5 year, with grade of tumor (P-value 0.001), lymph node metastases (P-value 0.001), invasion of other visceral organs(P-value 0.018) and recurrence (P-value 0.001)were associated with decreased survival. In conclusion, pancreatic neuroendocrine tumors have favorable long-term survival after surgical resections even in the presence of liver metastases depending on the grade of differentiation of tumor and lymph node metastases rather than liver metastases and other factors